Postural Effects on the Mental Rotation of Body-Related Pictures: An fMRI Study - Qu, Fangbing; Wang, Jianping; Zhong, Yuan; Ye, Haosheng (Frontiers in Psychology, 2018)
This study investigated the embodied effects involved in the mental rotation of pictures of body parts (hands, feet). Blood oxygen level-dependent (BOLD) signals were collected from 18 healthy volunteers who performed mental rotation tasks of rotated drawings of hands under different arm postures. Congruent drawings of hands (those congruent with left-hand posture) evoked stronger activation in the left supplementary motor area (SMA), left precentral gyrus, and left superior parietal lobule (SPL) than did incongruent drawings of hands. Congruent drawings of hands (those congruent with right-hand posture) evoked significant activation in the left inferior parietal lobule (IPL), right SMA, bilateral middle frontal gyrus (MFG), left inferior frontal gyrus (IFG), and bilateral superior frontal gyrus (SFG) compared to that evoked by the incongruent drawings of hands. Similar methodology was implemented with drawings of feet. However, no significant differences in brain activation were observed between congruent and incongruent drawings of feet. This finding suggests that body posture influences body part-related mental rotation in an effector-specific manner. A direct comparison between the medially and laterally rotated drawings revealed activation in the right IPL, left precentral gyrus, bilateral IFG, and bilateral SFG. These results suggest that biomechanical constraints affect the cognitive process of mental rotation.